Analysis Of Financial Statement Preparation Based On Sak Emkm At Parahyangan Muara Aman Cake Shop Lebong Regency - Harlina, Risa; Herlin, Herlin; Hanila, Siti (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2025)
The purpose of this study was to analyze the compliance of the Financial Statements of toko kue Parahyangan to the Financial Reporting Standards of Micro, Small and medium enterprises (SAK EMKM) in 2018. The method used in this study is a comparative descriptive study using a qualitative approach.technical data is collected through surveys and documentation. Based on the results of the study conducted based on interviews obtained by researchers from the financial statements prepared by the confectionery company Parahyangan lebong Regency, it is still very easy to record income and expenses, so it is not in accordance with the EMKM SAK in 2018. Based on the results of the analysis, it was found that the statement of financial position, Income Statement and memorandum of financial statements did not meet the requirements of the EMKM SAK in 2018.